Repetitive Transcranial Magnetic Stimulation for Major Depressive Disorder in Older Adults: Systematic Review and Meta-analysis - Valiengo, Leandro (2022)
Background Major depressive disorder (MDD) in older adults is a serious public health concern. Repetitive transcranial magnetic stimulation (rTMS) is a nonpharmacological intervention approved for MDD treatment in adults, but its value in older adults remains unknown. This study aims to systematically review and meta-analyze evidence of rTMS efficacy in MDD treatment among older adults. Methods We systematically reviewed the literature for randomized controlled trials (RCTs) and open-label studies assessing rTMS for the treatment of MDD in patients older than 50 years, published until June 2020. Random-effects meta-analyses using standardized mean differences (SMDs) were conducted to assess change in depression severity score (primary outcome), while odds ratios (ORs) were used to assess secondary categorical outcomes (response and remission). Additionally, univariate meta-regression analyses were performed to identify potential predictors of change in depression severity scores. Results Fourteen RCTs were included in meta-analyses and 26 studies (10 RCTs and 16 open-label studies) in meta-regression. Active rTMS was significantly superior to sham treatment for reduction of severity (SMD = 0.36; 95% CI = 0.13–0.60), as well as response (OR = 3.26; 95% CI = 2.11–5.04) and remission (OR = 4.63; 95% CI = 2.24–9.55). Studies were of moderate to high quality, with funnel plots and Egger’s regression test not suggestive of publication bias. In meta-regressions, higher mean age and number of sessions were significantly associated with greater improvement. Conclusions Our results support that rTMS is an effective, safe, and well-tolerated treatment for MDD in older adults and that it should be considered in the treatment of this vulnerable population.